Geminivirus-Derived Vectors as Tools for Functional Genomics - Bhattacharjee, Bipasha; Hallan, Vipin (Frontiers in Microbiology, 2022)
A persistent issue in the agricultural sector worldwide is the intensive damage caused to crops by the geminivirus family of viruses. The diverse types of viruses, rapid virus evolution rate and broad host range makes this group of viruses as one of the most devastating in nature, leading to millions of dollars’ worth of crop damage. Geminiviruses have a small genome and can be either monopartite or bipartite, with or without satellites. Their ability to independently replicate within the plant without integration into the host genome and relatively easy handling make them excellent candidates for plant bioengineering. This aspect is of great importance as geminiviruses can act as natural nanoparticles in plants which can be utilized for a plethora of functions ranging from vaccine development systems to geminivirus induced gene silencing (GIGS), through deconstructed viral vectors. Thus, the investigation of geminiviruses is pertinent to understanding their crucial roles in nature and subsequently utilising them for beneficial purposes. This review, therefore, highlights some of the characteristics of these viruses that can be deemed significant and the subsequent successful case studies for exploitation of these potentially significant pathogens for role mining in functional biology.